INTEREST IN MOBILE BANKING AND THE INFLUENCE OF RISK PERCEPTION - Wildoms Sahusilawane; Khaeruman Khaeruman; Harry Ramadhani (Jurnal Ekonomi, 2023)
The Covid-19 epidemic has prompted the government to enact a number of regulations as a means of aiding in the effort to stop the virus's chain of transmission. Also, the Covid-19 epidemic necessitates that people convert transactions from cash to non-cash in order to avoid contracting the virus. With mobile banking available to handle non-cash transactions, technological advancements support this move. Using the use of perceived utility as a mediating variable, this study seeks to understand how perceived risk and government backing affect interest in utilizing mobile banking. In this kind of quantitative research, data is collected using a questionnaire and processed using SEM-PLS (Structural Equation Modeling-Partial Least Square) software. The findings of the study demonstrate.